Mechanisms of histamine stimulated secretion in rabbit ileal mucosa. Issue 11 (November 1981) - Linaker, B D; McKay, J S; Higgs, N B; Turnberg, L A
Abstract : Histamine is present in high concentrations in the intestine and we investigated the possibility that it might have a role here in intestinal transport. When added to the basal side of rabbit ileal mucosa in vitro histamine (10(-4)M) induced a short-lived increase in electrical potential difference and short circuit current. It inhibited net chloride absorption but did not influence sodium transport. Alkali secretion, measured by a pH stat technique, was inhibited, suggesting that bicarbonate secretion was reduced. Both the electrical and ion flux responses to histamine were blocked by the H1 receptor blocker diphenhydramine, but not by the H2 receptor blocker cimetidine. The presence of specific H1 histamine receptors was further supported by shifts in the dose-response curve to histamine by four different concentrations of diphenhydramine. Calculation of a pA2 value from these "Schild' plots provided a figure of 7.85, which is similar to that for H1 receptors in other tissues. Aminoguanidine, a histaminase blocker, had no electrical effects alone but shifted the histamine dose response curve to the left. These studies indicate that histamine inhibits chloride absorption and alkali secretion, possibly by influencing a chloride/bicarbonate exchange process, through specific mucosal H1 receptors. Enhancement of histamine effects by a histaminase inhibitor suggests that histaminases are present in the intestinal mucosa and supports the possibility of a role for endogenous histamine in influencing ion transport. The observations indicate a mechanism by which absorption might be impaired in diseases in which histamine is liberated locally in the intestine.